Comparação de diferentes protocolos de treinamento físico nas atividades da vida diária em indivíduos com doença pulmonar obstrutiva crônica - Marrara, Kamilla Tays (2007)
Objective: To compare the effects of different physiotherapeutic intervention during simulation of activities of daily living (ADL) in patients with chronic obstructive pulmonary disease (COPD) moderate to severe. Methods: Thirty one patients with COPD (30%≤forced expiratory volume in first second (FEV1)<80% of predict), randomized in: Group PT (GPT, n=8): physical training (PT) in treadmill for 30 minutes; Group NIV (GNIV, n=9): PT associated to non-invasive ventilation (NIV) for 30 minutes; Group MT (GMT, n=8): PT of upper-limb and Control Group (CG, n=6), enduring six weeks, three times for week. In the test of ADL simulated: to erase blackboard, catch weight, elevate weight, sweep, to climb steps and walk in the treadmill, realizing five minutes each activity, except climb steps and walk with duration of six minutes. Results: Intragroup analysis: significative reduction of E/MVV in the post-treatment for PTG and NIVG in basal and walk. The MTG showed significative decrease erasing the blackboard and walk, being similar as for O2/ O2max. The dyspnea showed significative reduction for PTG to the walk, and increase in the CG post-treatment. The number of climbs on the steps redu